Removal of toxic methylene blue dye from aqueous solutions by adsorption technique using magnetic loaded tea waste and its sodium alginate composite microspheres - Guven, Meltem; Isik, Birol; Cakar, Fatih; Cankurtaran, Ozlem (SPRINGER, 2025)
This study presents the utilization of Fe3O4-doped black tea waste (TW) as an efficient, sustainable, and cost-effective adsorbent for the extraction of MB dye from wastewater, alongside the formulation of composite microbeads created by incorporating varying ratios of the black tea-magnetite mixture into sodium alginate (SA), a natural biopolymer. The characterization of composite microbeads was performed using FTIR-ATR, SEM, EDX, and pHpzc analyses. The surface charge of the adsorbent surface was determined as 6.43 from pHpzc. From the optimum condition studies, the contact time (60 min), adsorbent dosage (0.1 g/50 mL), and the initial pH (congruent to 7) were determined. The raw data were utilized in various non-linear isotherm and kinetic models. The correlation coefficients and error functions indicated that the Langmuir model is the most suitable isotherm model for the adsorption process, with a maximum adsorption capacity of 41.28 mg g-1 for the SA/TW/Fe3O4/30 composite microspheres at 298 K. The kinetic and error results indicated that the process adhered to a pseudo-second-order kinetic model. The thermodynamic characteristics indicated that the adsorption process was spontaneous (Delta Go=-25.09\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${\Delta G} {o}=-25.09$$\end{document} kJ mol-1) and endothermic (Delta Ho=+9.03\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$${\Delta H} {o}=+9.03$$\end{document} kJ mol-1). Moreover, reusability investigations indicated that the composite microbeads can be utilized multiple times. Following the tenth cycle, the adsorption efficiency fell by 32.33%, resulting in a value of 51.23%. The findings indicate that the developed unique, sustainable, and cost-effective composite microbeads serve as a prospective and highly efficient adsorbent for the elimination of cationic contaminants from wastewater.
Keywords: Adsorption; Tea waste-magnetite; Sodium alginate; CATIONIC DYES; EQUILIBRIUM; ISOTHERM; Environmental Sciences & Ecology